On The Job Training Assistance at UPTD SDN 34 Pakere to Improve Teacher Competence in Physical Activity-Based Learning - Arga; La Ode Ahmad Yusran; Muhammad Arkanul Arba'; Charmila Tandi Rerung; Siti Nurhalizah Mutia Aulria; A. Sakti Safitri; Fatimah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2026)
Teachers are the main actors in implementing effective and meaningful learning for students. At UPTD SDN 34 Pakere, teachers have shown high dedication in carrying out their teaching duties but still face challenges in integrating physical activities into daily learning processes. Limited understanding of physical activity-based learning methods and lack of practical experience in implementing them are the main obstacles. This Community Service activity aims to improve teacher competence through on-the-job training (OJT) assistance in integrating physical activities into classroom learning. The implementation method uses a descriptiveparticipatory approach involving 12 teachers from UPTD SDN 34 Pakere. The activity was carried out through stages of socialization, practical workshops, implementation assistance in the classroom, and joint reflection. Data collection techniques were carried out qualitatively through direct observation, interviews, and activity documentation. The results showed that OJT assistance was able to increase teachers’ understanding of the importance of integrating physical activity in learning, improve practical skills in designing and implementing physical activitybased learning, and increase teachers’ confidence in innovating in the classroom. Teachers began to understand that physical activity is not only important for student health, but can also improve concentration, learning motivation, and student learning outcomes. The OJT approach that provides direct assistance in the field has proven effective in helping teachers overcome technical barriers and improve the implementation of more active and enjoyable learning. This activity shows that OJT assistance can be an applicable and sustainable teacher professional development strategy in elementary school environments.